Islam and Iconoclasm: Ibrāhīm and the Destruction of Idols in the Qurʾān - Alhassen, Leyla Ozgur (Religion and the arts, 2019)
AbstractIn the Qurʾān, Ibrāhīm is portrayed as breaking the idols that his people worship (21:51-73), a story that comes at the crossroads of a number of ethical issues, including the freedom of belief. In this study, I examine the issue through a number of different lenses: Qurʾānic commentary (tafsīr on the story), art history (Islam, art and iconoclasm), legal opinions (jurisprudence), philosophical approaches (civil disobedience), and literary analysis (focused on idolatry and Ibrāhīm in the Qurʾān). In looking at the issue from these various perspectives, I argue that analyzing the story as a form of civil disobedience, while using literary analysis, lends new insights and gives modern readers tools with which to bridge some of the moral and ethical issues at play in the story of Ibrāhīm breaking his people's idols.